Imaginative Strangeness in the Poetry of Qeis bin Al Mulawah - محمد عبد اللطيف المشهداني, ميادة; عبد الودود عثمان الحمداني, إياد (Al-Adab Journal, 2018)
Platinic love, that revealed what is called platonic courtship, had a great deal of attention by the writers, literary people, and researchers. It has a huge impact in the hearts of the poets in the Amawi era especially "Layla's Mad". The purity and honest love and the end of life for the sake of the beloved was a characteristic of platonic courtship poets which made it unforgettable.This study sheds the light on imaginative strangeness which is related to irrational worlds and the change in usual performance into an image in the model of platonic love as represented in the poetry of Qeis bin Al Mulawah who is also known as "Layla's Mad". The study tries to analyze some of the elements that generate poetics. Hyperbole is considered to be a criteria to achieve strangeness in this study.The loving poet was still suffering from pain and deprivation of separation because of his honesty and loyalty to his beloved. He suffered from strangeness because of his great love to Layla to the extent that he imagined this world as prison. He felt as if he is a stranger among his people. He preferred to live with the ghost of his beloved wandering aimlessly in the desert and leaving behind the most beautiful images and words of the greatest love in his poetry.